EFFECT OF PLASMA SEMINAL FRACTIONS, BASED ON MOLECULAR WEIGHT, ON THE INDUCTION OF OVULATION IN LLAMAS (LAMA GLAMA) - Vásquez E., Martha (2008)
The present study was conducted to evaluate the effect of different fractions of llama seminal plasma, based on the molecular weight (MW), on the ovulation. Fifty four female adult llamas without calf at foot and in good reproductive conditions were used. The animals were bearing a >7 mm dominant follicle determined by ultrasound diagnosis during a three consecutive days. Females were randomly distributed in six groups: A, fraction of seminal plasma with MW >30 kDa; B, fraction of seminal plasma with MW >10 and <30 kDa; C, fraction of seminal plasma with MW >5 and <10 kDa ; D, fraction of seminal plasma with MW <5 kDa; E, complete plasma seminal; and F, PBS. Animals were treated with a 1.5 ml solution of the corresponding fraction or placebo via i.m. Ovarian ultrasound was performed at day 2 and 9 post-treatment to determine the ovulation rate and the size of the corpora lutea. Ovulation rate was 100% in groups A and E, 11.1% in group B and 0% in the other groups. No statistical differences were observed between groups on the size of the corpus luteum. The results indicated that the plasma seminal fraction with molecular weight >30 kDa induce ovulation in llamas.